2020
DOI: 10.1080/1828051x.2020.1738966
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nucleotides administration on growth performance and immune response of post-weaning piglets

Abstract: The aim of this study was to assess the effect of nucleotides administration on growth performance and immune response in post-weaning piglets. Twenty-eight male weaned piglets, homogeneous for age and weight were randomly allocated to two experimental treatments. Treated group (T) was daily orally administered 0.8 g/head of a mixture of nucleotides suspended in 2.1 mL water solution; while control group (C) received 2.1 mL saline solution. Body weight (BW) and average daily gain (ADG) were individually record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 23 publications
(27 reference statements)
1
8
0
Order By: Relevance
“…Ileum is highly susceptible to pathogens and its structural and functional changes linked to nutraceutical administration are of a predictive value to evaluate intestinal defensive responsiveness [ 47 ]. Published papers targeted the ileum rather than jejunum when evaluating the efficacy of feed additives with presumed beneficial effect on performance and inflammatory- and immune-related parameters [ 10 , 48 ] because in differentiated and matured ileum, immunological structures like Peyer’s patches are much more abundant [ 49 ]. The significant reduction in TLR4 expression in IPP we observed in our trial could be explained by a reduced exposure of the enterocytes to pathogenic bacteria thanks to the decoy role of MOS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ileum is highly susceptible to pathogens and its structural and functional changes linked to nutraceutical administration are of a predictive value to evaluate intestinal defensive responsiveness [ 47 ]. Published papers targeted the ileum rather than jejunum when evaluating the efficacy of feed additives with presumed beneficial effect on performance and inflammatory- and immune-related parameters [ 10 , 48 ] because in differentiated and matured ileum, immunological structures like Peyer’s patches are much more abundant [ 49 ]. The significant reduction in TLR4 expression in IPP we observed in our trial could be explained by a reduced exposure of the enterocytes to pathogenic bacteria thanks to the decoy role of MOS.…”
Section: Discussionmentioning
confidence: 99%
“…With the purpose to sustain animals' health status and performance, the supplementation of different molecules, compounds and bioactive substances have been investigated in recent years. Nowadays, several classes of feed additives are available and widely employed in pig farming such as probiotics [7], prebiotics [8], postbiotics [9], nucleotides [10] and phytobiotics [11].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, piglets undergo oxidative stress and inflammation after weaning that can further participate in poor performance [10]. These adverse outcomes can be alleviated by supplementing with abundant sources of bioactive compounds [10][11][12][13]. Brown seaweed Ascophyllum nodosum (A. nodosum) is a rich source of natural antioxidants [14] and antimicrobials [15], which can inhibit or impede oxidative damage by neutralizing free radicals in the cell [16].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, in a study by Jang and Kim (2019) [ 26 ], a supplementation of 50 and 150 mg/kg of nucleotides to newly weaned pigs increased ADG in the first week post-weaning. In another study, Perricone et al (2020) [ 27 ] found that a higher dose (0.8 g) of nucleotide in post-weaning increases ADG, BW, and FI. These studies were mostly focused on the post-weaning phase, none of these investigated the effect starting from the suckling phase.…”
Section: Discussionmentioning
confidence: 99%
“…Their higher multiplicative and productive activity in supplemented pigs may also explain the better ability of Peyer’s patches to produce more inflammatory cytokines of post-weaning pigs reared in poor environmental condition [ 45 ] and the increased IgA production [ 4 ]. Conversely, this mechanism was not more active in standard rearing conditions [ 27 ], where Peyer’s Patches activation of inflammatory cytokines was not seen with the addition of nucleotides, while this addition promoted growth response of piglets.…”
Section: Discussionmentioning
confidence: 99%